Archaeologies of listening - Schmidt, Peter R.; Schmidt, Peter R.; Kehoe, Alice Beck; Kehoe, Alice Beck (Florida scholarship online, 2019)
'Archaeologies of Listening' provides a fresh and bold look at how archaeologists and heritage managers may enhance their capacity to interpret and understand material culture and heritage values. By listening closely to indigenous voices and to those who have long-term relationships with the landscape, deeper empirical understandings are brought to interpretations. Drawing on the founding principles of anthropology, this work demonstrates the value of cultural apprenticeship, an almost forgotten part of archaeological practice